Sauce Filler Machine Automatic Screw System Equipped with Electrical Control Unit - Syeihan Syahrul Syah; Muhammad Irfan Maulana; Adly Fitra Ainurroji; Mohamad Rizqi Ardiansyah; Alfian Reynaldi; Agung Prijo Budijono (Journal of International Conference Proceedings (JICP), 2018)
The purpose: The Purpose of this research is to create prototype of automatic Sauce filler machine with threaded drive system integrated with electric motor, as piston driver Methodology This research was comitted by designing an automatic filling machine, with a filler mechanism using a screw-driven piston technology, where the thread is rotated by an electric motor integrated with the timer.timers are used to charge more precise out, electric motors and threaded systems can make fillers more power efficient than hydraulic or pneumatic system. The filling system also utilizes the combination of two one-way valves, where the charging process is divided into 2 steps: suction step and press Result, This Research resulted of prototype of automatic filler machine, within 1.2 kg/min flow rate, for the 150 g of sauce capacity storage takes 7.5 second . This machine is equipped with an easy charging method that is operated using only 1 button. the productivity of performance machine has been increased 2 times The findings, This Research finds the design and prototype of a more precise and power-saving automatic charging machine by using a screwmounted piston system, which is suitable for home industry. Keywords: filler machine, screw, piston filler, sauce